Analisa Usahatani Padi Ketan (Oryza sativa glutinosa) (Studi Kasus di Kelompok Tani Sri Rahayu Desa Margamulya Kecamatan Bongas Kabupaten Indramayu) - Neneng Sri Mulyati; Pandu Sumarna (Paspalum: Jurnal Ilmiah Pertanian, 2019)
The research aims to determine the cost of production, acceptance, profit, RC Ratio (Revenue Cost Ratio), and feasibility (ability) of glutinous rice farming.  The research method is to use a descriptive survey with a census of sampling techniques against members of the farmer group Sri Rahayu Margamulya village Bongas Sub-district of Indramayu district that planted glutinous rice with 11 people.  Based on the results of the research can be known that the average total cost of glutinous rice farming is Rp. 29,313,151.52, the average admission is Rp. 47,836,363.64, the average profit is Rp. 18,523,212.12, and the R/C of its farming is 1.63, As well as the ability gained by farmers is 63% per season higher than the Bank rate prevailing at the time 1.5% per month. So it can be concluded that glutinous rice farming is profitable and worthy to be cultivated.